2018
DOI: 10.1007/s10616-018-0211-y
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue extract shows potential for wound healing: in vitro proliferation and migration of cell types contributing to wound healing in the presence of adipose tissue preparation and platelet rich plasma

Abstract: Growth factors are the key elements in wound healing signaling for cell migration, differentiation and proliferation. Platelet-rich plasma (PRP), one of the most studied sources of growth factors, has demonstrated to promote wound healing in vitro and in vivo. Adipose tissue is an alternative source of growth factors. Through a simple lipoaspirate method, adipose derived growth factor-rich preparation (adipose tissue extract; ATE) can be obtained. The authors set out to compare the effects of these two growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 46 publications
3
20
0
Order By: Relevance
“…As described by Lopéz et al, bFGF, VEGF, epidermal growth factor (EGF), IGF-1, IL-6, PDGF-BB, TGF-ß and TNFα are present at significantly lower concentrations in ATE compared to PRP [19]. Our study confirmed this for bFGF, VEGF, IGFBP-1 and PDGF (Table 2).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…As described by Lopéz et al, bFGF, VEGF, epidermal growth factor (EGF), IGF-1, IL-6, PDGF-BB, TGF-ß and TNFα are present at significantly lower concentrations in ATE compared to PRP [19]. Our study confirmed this for bFGF, VEGF, IGFBP-1 and PDGF (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…With a comparable incubation time of 24 h, the protein content in our study was about four times higher than reported by Sarkanen et al (4.05 ± 0.08 mg/mL vs. 1.12 ± 0.19 mg/mL). Lopéz et al found an almost 10 times lower mean protein concentration of 0.49 ± 0.16 mg/mL for ATE [19]. The increased protein concentration in our study may be due to an optimized production process with continuous rotation during incubation, fractional filtration and final dialysis.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…FGF2 can also stimulate the differentiation of ADSCs to endothelial cells to enhance angiogenesis . FGF is found in increased volumes in PRP and is released rapidly from PRP at high concentrations with maximum levels detected at 1 hour suggesting that it may assist in the early phases of wound healing. One animal study demonstrated a synergistic effect of PDGF and FGF in enhancing angiogenesis and the growth of functional and stable vascular networks in mice .…”
Section: Growth Factors and Their Role In Prp And Fat Synergymentioning
confidence: 99%